Pemodelan Potensi Perbandingan Pencucian Uang: Tata Kelola Publik dan Dinamika Budaya sebagai Faktor Kritis - Alfarizi, Muhammad; Zalika, Zela (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2024)
Corruption and money laundering are global issues with significant economic impacts, particularly in Asia and Europe. This comparative study explores the relationship between national culture, public governance, and money laundering potential, focusing on cultural differences between the East and West. Utilizing a quantitative approach, the study analyzes secondary data from the 2023 Basel Anti-Money Laundering (AML) Index, covering 49 Asian and 47 European countries. Structural Equation Modelling-Partial Least Square (SEM-PLS) is employed for analysis. The findings reveal that cultural dynamics significantly and positively influence public governance. However, public governance and cultural dynamics do not directly affect the potential for money laundering. Mediation tests indicate that public governance mediates the relationship between cultural dynamics and money laundering potential. A Multigroup Analysis (MGA) test highlights significant regional differences, particularly in the influence of public governance on money laundering potential. The study underscores the need for multifaceted strategies to combat money laundering globally, emphasizing international collaboration, public education, governance enhancement, and technological advancement. Recommendations for the Financial Action Task Force (FATF) include strengthening cross-country cooperation and improving public governance frameworks to mitigate global money laundering risks effectively.